Reclaiming urban space: Socio-economic dynamics in the Car-Free Day Boulevard of Makassar - Misbawati; Ahmadin (Jurnal Ekonomi dan Riset Pembangunan, 2025)
One interesting urban phenomenon is urbanization and its resulting impacts, often neglecting the function of public space for the sake of motorized vehicles. This results in reduced social interaction and local economic opportunities. Therefore, the Car Free Day program exists as a form of tactical urbanism to reclaim temporary street space by transforming it from a transportation corridor into a public space filled with activity. This article analyzes the practices of social interaction and economic activity that occur in this area, as well as the perceptions of visitors and business owners regarding the meaning of this public space. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that the practice of utilizing space on the Boulevard highway has created a new socio-economic ecosystem in Makassar City. This government program also motivates the restoration of the social function of the road and forms a form of local economic empowerment. The findings of this study can even serve as recommendations for the city government for sustainable public space planning oriented towards fulfilling the social rights of city residents.